Analysis of the Effect of Marketing Mix on Consumer Decisions to Use Service Services at Anugerah Perdana Palu Official Workshop - Leopold Merik; Nasrulhak Akkas; Guasmin Guasmin (Universitas Muhammadiyah Palu, 2021)
This study aims to see whether there is a relationship between the independent variables, namely the marketing mix including product, price, promotion, location, people/HR, physical evidence, and processes, and the dependent, namely the consumer decision at Bengkel Anugerah Perdana Monginsidi Palu. Using multiple regression analysis techniques.